Ultrasound of the chest and mediastinum in children, interventions and artefacts. WFUMB review paper (part 3) - Fang, Cheng; Jaworska, Joanna; Buda, Natalia; Ciuca, Ioana Mihaiela; Dong, Yi; Feldkamp, Axel; Jüngert, Jörg M.; Kosiak, Wojciech; Mentzel, Hans Joachim; Pienar, Corina; Rabat, Jorge S.; Rafailidis, Vasileios; et al. (Medical Ultrasonography, 2022)
Ultrasound (US) is an ideal diagnostic tool for paediatric patients owning to its high spatial and temporal resolution, realtime imaging, and lack of ionizing radiation and bedside availability. The lack of superficial adipose tissue and favourable acoustic windows in children makes US the first line of investigation for evaluation of pleural and chest wall abnormalities.In the first part of the topic the technical requirements were explained and the use of ultrasound in the lung and pleura in paediatric patients were discussed. In the second part lung parenchymal diseases with their subpleural consolidations are reflected. In the third part, the use of ultrasound for chest wall, mediastinum, diaphragmatic diseases, trachea, interventions and artifacts in paediatric patients are summarized.
CRIS-Team Scopus Importer:2022-02-25